“Men will sexualize you anyway, so why shouldn’t I profit from it?”: exploring the well-being impacts of sex work on the subscription-based platform, OnlyFans - Anna Júlía Magnúsdóttir 1999- (2023)
Iceland witnessed a viral discussion in 2021 regarding the subscription-based platform, OnlyFans (OF) known for its link to mainstream digital sex work and creators of sexually explicit material (SEM). Concerns arose about creators profiting from such material, even leading to disrespectful commentary towards them. Creators defended their work, requesting respect. Research on online sex work is severely lacking, and therefore, in this study, the goal was to examine the well-being impacts of selling SEM on OF. Qualitative, unstandardized interviews were conducted, and the results showed five main findings. Most participants said their experience working on OF was mainly positive. Most negative experiences came from not being accepted in society. OF creators say recourses are limited, such as therapists and psychologists that understand sex work. There are some challenging sides to the job, yet creators feel hesitant to discuss those since society seems to anticipate their failure. Creators stressed that making “easy money” on OF is a misconception; substantial income requires hard work. The findings suggest that misconceptions about online sex work, stemming from its stigma, can lead to a deficit of support and resources available for SEM creators. Keywords: OnlyFans, sex work, sexually explicit material, well-being effects, stigma Árið 2021 kom upp umfangsmikil umræða á Íslandi um OnlyFans (OF) sem er Internet-vettvangur þar sem einstaklingar geta keypt áskrift að efni frá þeim sem bjóða upp á það, gegn mánaðarlegri greiðslu. Vefsíðan hefur þó aðallega verið tengd við framleiðslu og sölu á klámi. Skortur er á rannsóknum á net-kynlífsvinnu og er markmið þessarar rannsóknar að kanna áhrif þess að vinna í klámi á OF á vellíðan. Eigindleg, óstöðluð viðtöl voru framkvæmd og niðurstöður sýndu fimm meginþemu. Flestir þátttakendur sögðu reynslu sína af OF vera mestmegnis jákvæða. Þær neikvæðu upplifanir sem tengdust starfinu máttu flestar rekja til fordóma samfélagsins. Þátttakendur töldu að skortur væri á úrræðum ...